2015
DOI: 10.1155/2015/486467
|View full text |Cite
|
Sign up to set email alerts
|

Paleopathology and Nutritional Analysis of a South German Monastery Population

Abstract: The monastery of Attel, Upper Bavaria, which was founded in AD 1030, harbours a series of crypt burials from the time period between AD 1700 and 1750. Due to a restoration of the church, 16 crypts had to be removed and were subjected to an extensive anthropological-paleopathological and isotope analysis. The 16 crypts contained 19 burials in open wooden coffins. All bodies were covered by an extensive layer of calcium carbonate. Despite this “treatment,” bone and teeth were excellently preserved (mean degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Body height can be used as a proxy for nutrition and health during adolescence even though the basic range largely depends on genetics. With an average stature of 169.3 cm for males (n = 3) and 163.4 cm for females (n = 5), the Sommersdorf individuals fit very well into the frame given by larger medieval and post-medieval series in Bavaria [ 92 – 96 ] ( Table 5 ). Due to the estimation of body height using the femur, the male individuals from Sommersdorf seem to be smaller than the Bavarian average while the female individuals are taller.…”
Section: Discussionmentioning
confidence: 68%
“…Body height can be used as a proxy for nutrition and health during adolescence even though the basic range largely depends on genetics. With an average stature of 169.3 cm for males (n = 3) and 163.4 cm for females (n = 5), the Sommersdorf individuals fit very well into the frame given by larger medieval and post-medieval series in Bavaria [ 92 – 96 ] ( Table 5 ). Due to the estimation of body height using the femur, the male individuals from Sommersdorf seem to be smaller than the Bavarian average while the female individuals are taller.…”
Section: Discussionmentioning
confidence: 68%
“…Besides the multiple metastases and the tooth loss, this investigation showed only a few additional disorders; most cases of intra vitam tooth loss in historic populations is due to poor dental health e.g. extensive chronic periodontitis or lack of dental hygiene [11], but remains unproven in this case.…”
Section: Further Pathological Findingsmentioning
confidence: 69%
“…Otherwise, during the first decades of his life, he did not suffer from obvious major disorder, at least that manifested in his skeleton, except for the complete loss of teeth of the maxilla and several teeth of the mandible. This, however, was quite a frequent occurrence in advanced aged individuals at this time and included monastic communities, probably due to poor dental health care and lack of oral hygiene [11]. Beyond this, his most important health problem was the development of prostatic cancer which may have affected him symptomatically in his very final years or even only for his final months of life.…”
Section: Scenario Of the Life Of Abbot Balduinmentioning
confidence: 95%
See 1 more Smart Citation
“…A study of remains of 18th-century inhabitants of a central European monastery (who would also have enjoyed high rank and status) found that they had an osteologically estimated mean stature of ca. 171 cm (5.61 ft.), while their local contemporaries averaged 162-165 cm (5.31-5.41 ft.) (Nerlich et al 2015). In contrast, a typical, well-nourished Finnish man today has an average height of 180.7 cm (5.93 ft.) (Saari et al 2011).…”
Section: Biological Evidence Indicates High Statusmentioning
confidence: 96%